Confrontation between Believers and Young “Godless” as a Factor of Intergenerational Rift in Russian Village in 1920s - A. A. Slezin (Научный диалог, 2023)
The relationship between representatives of the generations of the “revolutionary turning point” (born at the turn of the 19th-20th centuries) and “children of the revolution” (those whose childhood fell on the first post-revolutionary fifteen years) is analyzed. The role of the young “godless” of the 1920s in the evolution of the moral state of the peasant “fathers” is studied. The role of the young “godless” of the 1920s in the evolution of the moral state of the peasant “fathers” is studied. Attention is paid to the theoretical substantiation of the role of the pioneers in the formation of the “new man”, their practical efforts in this direction and the reaction of the peasantry. It is shown that the spiritual heritage, which, according to the rules of continuity of development, the generation of the “revolutionary turning point” was called upon to pass on to its successors, in real life was rejected by active representatives of the younger generation. The confrontation between young “godless” and adherents of traditional religions significantly influenced the strengthening of the intergenerational rift in the Russian village. An analysis of the experience of forming the foundations of the pioneer movement and identifying the causes of the exacerbation of intergenerational conflict in the Russian countryside (including children’s anti-religious activities) are of particular relevance in connection with the search for a model of education that meets the modern demands of the state and society.